2007
DOI: 10.2353/ajpath.2007.070052
|View full text |Cite
|
Sign up to set email alerts
|

Cholesterol Accumulation Is Associated with Lysosomal Dysfunction and Autophagic Stress in Npc1−/− Mouse Brain

Abstract: Niemann-Pick type C (NPC) disease is an autosomal recessive disorder caused by mutations of NPC1 and NPC2 genes. Progressive neurodegeneration that accompanies NPC is fatal, but the underlying mechanisms are still poorly understood. In the present study, we characterized the association of autophagiclysosomal dysfunction with cholesterol accumulation in Npc1 ؊/؊ mice during postnatal development. Brain levels of lysosomal cathepsin D were significantly higher in mutant than in wild-type mice. Increases in cath… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
154
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(179 citation statements)
references
References 73 publications
24
154
0
Order By: Relevance
“…neurodegeneration in cathepsin D-deficient brain (42). In addition, a npc1 gene-disrupted mouse model for Niemann-Pick Type C disease showed neurodegeneration, increased numbers of AVs, and increased levels of cathepsin D and cathepsin B in the brain, indicating that cholesterol accumulation results in altered lysosome function and neuronal cell death (43). These studies support our findings that lysosomal dysfunction results in reduced turnover of AVs leading to autophagic stress-induced neuronal death, an effect that can be attenuated by blocking AV synthesis.…”
Section: Discussionsupporting
confidence: 78%
“…neurodegeneration in cathepsin D-deficient brain (42). In addition, a npc1 gene-disrupted mouse model for Niemann-Pick Type C disease showed neurodegeneration, increased numbers of AVs, and increased levels of cathepsin D and cathepsin B in the brain, indicating that cholesterol accumulation results in altered lysosome function and neuronal cell death (43). These studies support our findings that lysosomal dysfunction results in reduced turnover of AVs leading to autophagic stress-induced neuronal death, an effect that can be attenuated by blocking AV synthesis.…”
Section: Discussionsupporting
confidence: 78%
“…24 The activation of basal autophagy was found to be accompanied by impaired degradation of long-lived proteins, abnormal levels of the lysosomal enzyme cathepsin D, and accumulation of undigested polyubiquitinated proteins in the endolysosomal and lysosomal fraction. 22 These findings indicate that disruption of lipid trafficking in NP-C results in a global enhancement of autophagy that is, however, not sufficient to handle the quantity of proteins targeted for degradation. Importantly, induction of autophagy in NPC1-deficient cells is associated with an increased expression of Beclin-1, whereas mTOR signaling remains unchanged.…”
Section: Reviewmentioning
confidence: 88%
“…19,20 Consequently, impairment of these proteins leads to the endosomal and lysosomal accumulation of cholesterol and secondary storage of glycophospholipids in the brain and other organs. 19 In recent years, studies have demonstrated accumulation of autophagosomes in degenerating neurons of NPC1 knockout mice, [21][22][23] primary fibroblasts derived from NP-C patients, 23 and NPC1-deficient cell culture models. 24 The activation of basal autophagy was found to be accompanied by impaired degradation of long-lived proteins, abnormal levels of the lysosomal enzyme cathepsin D, and accumulation of undigested polyubiquitinated proteins in the endolysosomal and lysosomal fraction.…”
Section: Reviewmentioning
confidence: 99%
“…Interestingly, our results revealed that the numbers of secondary lysosomes as well as of the autophagy markers LC3-II and beclin-1 are higher in both the cerebellum and hippocampus of Npc1 Ϫ/Ϫ mice compared with controls as reported in earlier studies. 49,50 Because autophagy can be induced during both survival and death of cells, 9,65 the significance of the enhanced autophagic pathway in Npc1 Ϫ/Ϫ mice remains to be defined.…”
Section: Discussionmentioning
confidence: 99%
“…As for the autophagy marker LC3, it is known that after induction of autophagy this protein is modified from its cytosolic LC3-I form to a rapidly migrating, lipid-conjugated LC3-II form associated with autophagosomal membranes. 48,49 Beclin-1, on the other hand, is part of the class III phosphatidyl-inositol-3 kinase complex that participates in autophagosome formation. 50 Our results showed that levels of LC3-II and, to some extent, those of beclin-1 are increased in both the cerebellum and hippocampus of Npc1 Ϫ/Ϫ mice compared with controls (Supplemental …”
Section: Altered Cholesterol Distribution and Loss Of Neurons In Npc1mentioning
confidence: 99%